2020
DOI: 10.1097/md.0000000000021912
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder neuroendocrine carcinoma

Abstract: Gallbladder neuroendocrine carcinoma (GB-NEC) is a group of rare and heterogeneous neoplasms and there are few reports at present. We analyzed the clinical and pathological features of 7 patients with GB-NEC who were admitted to Zhejiang Provincial People's Hospital from January 2011 to October 2019. The median age of 7 patients was 58 years with male to female ratio of 1:2.5. Right upper quadrant discomfort was the main complaint and no patients presented carcinoid syndrome-related sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…As was the case in previous studies, patients enrolled in this study were predominantly female. 17 Although the clinical and pathological features were similar between NEC and ADC patients after PSM, the overall survival rates were still obviously lower in NEC patients 7,13,14,18 NEC patients in this study were divided into two groups according to age. In younger patients, the TNM stage was relatively late, but there was no significant difference (p = 0.522).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As was the case in previous studies, patients enrolled in this study were predominantly female. 17 Although the clinical and pathological features were similar between NEC and ADC patients after PSM, the overall survival rates were still obviously lower in NEC patients 7,13,14,18 NEC patients in this study were divided into two groups according to age. In younger patients, the TNM stage was relatively late, but there was no significant difference (p = 0.522).…”
Section: Discussionmentioning
confidence: 67%
“…As was the case in previous studies, patients enrolled in this study were predominantly female. 17 Although the clinical and pathological features were similar between NEC and ADC patients after PSM, the overall survival rates were still obviously lower in NEC patients 7 , 13 , 14 , 18…”
Section: Discussionmentioning
confidence: 95%
“…By analyzing the data of patients undergoing surgery in this group, it was found that cholecystectomy or radical cholecystectomy was feasible for stage I and II gallbladder carcinoma, including skeletonization of the biliary trigone, hepatoduodenal ligament, and wedge resection of the liver with a depth of 2 cm in the gallbladder bed, which was with a good prognosis. Expanded resection of gallbladder carcinoma had a poor prognosis even if the resection scope was wide (including extrahepatic bile duct, colon, duodenum, and liver IVV) [ 16 ]. A small number of patients survived for a long time when the right lobe of the liver was enlarged for gallbladder carcinoma.…”
Section: Analysis Of the Antigallbladder Carcinoma Activity Of The Ne...mentioning
confidence: 99%
“…The disease is predominantly diagnosed by postoperative pathology and immunohistochemistry. It is worth noting that some reports have reported a relationship between elevated tumor markers (such as CEA) and prognosis, as well as liver invasion[ 18 ]. Patient clinicopathological characteristics are summarized in Table 3 .…”
Section: Resultsmentioning
confidence: 99%